Association of fear-avoidance and self-efficacy on pain disability in individuals with co-morbid post-traumatic stress and chronic pain. (January 2022) - Devlin, Anna; Casey, Sara; Williams, Scott; Giummarra, Melita J
This study investigated relationships between post-traumatic stress symptoms (PTSS) and pain disability. Fifty people with chronic pain (probable PTSD, n = 22) completed measures assessing pain interference, PTSS, fear avoidance, and pain self-efficacy. We hypothesized that people with probable PTSD would have higher fear avoidance and lower pain self-efficacy; and that PTSS would be indirectly associated with pain disability via fear avoidance and self-efficacy. People with probable PTSD had higher fear avoidance, but there were no differences in self-efficacy, pain severity or disability. There was an indirect association between PTSS and pain disability via fear avoidance, but not via self-efficacy.